Indigenous African Aesthetics and the Ancestral Memory of African Americans in August Wilson’s The Piano Lesson - Sharma, Bed Nath (The Outlook: Journal of English Studies, 2026)
This article explores the relationship between identity and heritage in the context of African American history shaped by slavery and systematic discrimination in Wilson’s play The Piano Lesson. This relationship is portrayed in Wilson’s The Piano Lesson. To explore this relationship, this study raises two research questions: How are indigenous African aesthetics and indigenous African American aesthetics connected through the symbolism of the piano that stands for ancestral presence, communal identity, and rituals? In what ways does the ancestral memory shape the characters’ identities and actions? To answer these questions, this paper aims to trace the aspects of indigenous African aesthetics and ancestral memory in the play through the lens of Robert Francis Thompson’s theory of Indigenous African aesthetics, which excavates the ancestral presence, spiritually charged artefacts, and communal responsibility in the African American expression. Using a close textual analysis of dialogues, music, language and artefacts, the paper examines how Boy Willie and Berniece present their competing responses to the piano. The findings reveal that enacting and enlivening the artefact enable the restoration and continuity of ancestral memory.  Moreover, according to the indigenous African aesthetics worldview healing and continuity depend on the active remembrance, not as a burden but as a sustaining foundation for African American identity.